2021
DOI: 10.1093/molehr/gaab054
|View full text |Cite
|
Sign up to set email alerts
|

Soluble adenylyl cyclase inhibition prevents human sperm functions essential for fertilization

Abstract: Soluble adenylyl cyclase (sAC: ADCY10) has been genetically confirmed to be essential for male fertility in mice and humans. In mice, ex vivo studies of dormant, caudal epididymal sperm demonstrated that sAC is required for initiating capacitation and activating motility. We now use an improved sAC inhibitor, TDI-10229, for a comprehensive analysis of sAC function in mouse and human sperm. In contrast to caudal epididymal mouse sperm, human sperm are collected post-ejaculation, after sAC activity has already b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 41 publications
5
59
0
Order By: Relevance
“…Our results are consistent with others’ observations that the sAC and PKA pathways are important in regulating sperm capacitation in many species and that these pathways act, at least in part, by regulating pH i ( Puga Molina et al, 2017 ; Chavez et al, 2019 ; Matamoros-Volante and Trevino, 2020 ; Balbach et al, 2021 ). Carlson et al showed no changes in pH i induced by HCO 3 – in mouse sperm.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are consistent with others’ observations that the sAC and PKA pathways are important in regulating sperm capacitation in many species and that these pathways act, at least in part, by regulating pH i ( Puga Molina et al, 2017 ; Chavez et al, 2019 ; Matamoros-Volante and Trevino, 2020 ; Balbach et al, 2021 ). Carlson et al showed no changes in pH i induced by HCO 3 – in mouse sperm.…”
Section: Discussionsupporting
confidence: 93%
“…Our observation that the HCO 3 – -induced change in pH i was inhibited by a specific sAC inhibitor ( Balbach et al, 2020 , 2021 ) suggests that the main mechanism of pH i increase is through the sAC/cAMP/PKA pathway. This increase in pHi might further activate sAC, as Xie et al showed that sAC activity increases upon intracellular alkalinization ( Xie et al, 2006 ).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations